Does Delivery Location Matter? A National Study of the Impact of Dual Enrollment on College Readiness and Early Academic Momentum. Issue 4 (April 2021) - Hu, Xiaodan; Chan, Hsun-Yu
Background/Context: Although dual enrollment (DE) programs have indicated positive impact on various high school and postsecondary outcomes, access to DE programs remains unequal; historically marginalized students are less likely than other students to attempt college credits in high school. Despite DE being a widely adopted program at the state level, these programs vary greatly by eligibility criteria, funding models, delivery location, and modality. Purpose/Objective/Research Question/Focus of Study: Guided by prominent learning theories, we hypothesize that the influence of early DE on later educational pathways and outcomes may vary by the location in which DE is delivered. This study examines whether the delivery location of DE (i.e., on a college campus or otherwise) influences students' college readiness and first-year academic momentum in college, with a special focus on its heterogeneous effect among students of diverse racial and socioeconomic background. Research Design: Using the restricted-use data from High School Longitudinal Study of 2009 (HSLS:09), we use a quasi-experimental approach (i.e., inverse probability weighting models) with a nationally representative sample of students who have taken at least one DE course by 11th grade. Findings/Results: The findings reveal that students who took at least one DE course on a college campus do not differ in their cumulative high school GPA, in their probability of attending college, in whether they took developmental courses, in whether they attended college immediately after high school graduation, and in their probability of full-time enrollment when compared with those who took DE course(s) elsewhere. However, the findings are not applicable to all students of varying background defined by race/ethnicity and socioeconomic status. Conclusions/Recommendations: This study provides several implications: (1) Because DE courses taken on a high school or college campus equally fuel students' college readiness and early academic momentum, advising practices should acknowledge the benefits of DE courses regardless of delivery location. (2) DE participation with college exposure may particularly benefit students of higher socioeconomic status (SES), so interventions that offer holistic college experiences beyond academic work are needed to effectively prepare lower SES students for college life and accumulate academic momentum are needed. (3) States and educational entities should be mindful about the potential disparate effect of DE programs and provide regulation, oversight, and quality assurance so that these programs can narrow the postsecondary achievement gap.